2021
DOI: 10.3389/fmed.2021.636160
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Testing of 11,884 Healthcare Workers at an Acute NHS Hospital Trust in England: A Retrospective Analysis

Abstract: Healthcare workers (HCWs) are known to be at increased risk of infection with SARS-CoV-2, although whether these risks are equal across all roles is uncertain. Here we report a retrospective analysis of a large real-world dataset obtained from 10 March to 6 July 2020 in an NHS Foundation Trust in England with 17,126 employees. 3,338 HCWs underwent symptomatic PCR testing (14.4% positive, 2.8% of all staff) and 11,103 HCWs underwent serological testing for SARS-CoV-2 IgG (8.4% positive, 5.5% of all staff). Sero… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
2
17
0
1
Order By: Relevance
“…Many studies have sought to define the antibody response following SARS-CoV-2 infection ( 14 , 15 ). These include studies on hospitalized COVID-19 patients ( 16 19 ), asymptomatic individuals ( 20 , 21 ), and retrospective serological studies ( 22 25 ). The vast majority of infected individuals seroconvert and generate IgA, IgM, and IgG-specific antibodies within 3 weeks of infection ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have sought to define the antibody response following SARS-CoV-2 infection ( 14 , 15 ). These include studies on hospitalized COVID-19 patients ( 16 19 ), asymptomatic individuals ( 20 , 21 ), and retrospective serological studies ( 22 25 ). The vast majority of infected individuals seroconvert and generate IgA, IgM, and IgG-specific antibodies within 3 weeks of infection ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is critical to ensure the safety of HCWs not only to safeguard continuous disease control and treatment but also to ensure they do not transmit the virus under more frequent social communication conditions [ 17 ]. A retrospective analysis in England showed that overall infection level among HCWs was probably underestimated due to asymptomatic seroconversion [ 18 ]. In the aspect of COVID-19 vaccination, HCWs play an important role in vaccine propagation and education, and their vaccination willingness can also influence the attitude and uptake choice of the general population [ 15 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a paper published by Hanrath et al, it was concluded that, by comparing the healthcare workers who had no infection in the first wave with those who have been positive, the positivity rate was 0% among those who had the infection before, as compared to almost 14% among the healthcare workers who had not the infection before [2]. This is a strong proof that having had SARS-CoV-2 infection in the past does actually provide protection at least for a short time.…”
Section: Giovanni DI Perrimentioning
confidence: 99%